Romancing the “Mysterious Bonds of Syntax”:: Allegory and the Ethics of Desire in Douglas Glover’s “My Romance” and “Iglaf and Swan” - Beardsworth, Adam (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2005)
Douglas Glover posits that good fiction contains a rough tension between postmodern concerns with the structure of language and the meaning, or "aboutness," of the narrative. The philosophical premise of Glover's "My Romance" and "Iglaf and Swan" rests on the Sartrean notion that desire is ultimately a longing for nothingness. The "aboutness" of each story is the absence created by the death of a child, which triggers in the parent an existential confrontation with, and a desire to fill, the resultant void of nothingness. The narrative then becomes an allegory for the writing process itself. Just as the dead child becomes a symbol of absence with which the parent futilely seeks unification, language is only ever a linguistic signifier that can never reflect pure meaning. The desire to bridge the gap, or void, between signifier and signified can only be achieved through an ethical recognition of the other, which Glover demonstrates at both the thematic and textual levels.